Analisis Perbandingan Status Gizi Ibu Hamil Yang Mengkonsumsi Susu Ibu Hamil Dan Yang Tidak Mengkonsumsi Susu Ibu Hamil Selama Kehamilan Di Bpm Ny.Endang S Kota Kediri - Nita Dwi Astikasari; Wa Ode Sitti Apri Harliyanti (Journal for Quality in Women's Health, 2018)
Mother's nutritional status before and during pregnancy can affect the growth of the fetus being conceived. If the nutritional status of normal mothers in the period before and during pregnancy most likely will give birth to a healthy baby, enough months with normal weight. The purpose of this study to analyze the ratio of pregnant women who consume milk pregnant women with pregnant women who do not consume milk pregnant women on the nutritional status of pregnant women in BPM Ny.Endang S, Kediri. The research design used was observational with cross sectional approach. The population is pregnant mother of Trimester III with sample of 10 pregnant women consuming milk of pregnant mother and 10 pregnant women who do not consume milk of pregnant mother. The sampling technique used is accidental sampling. Data collection using questionnaire and observation. The results showed that the respondents who consumed the milk of pregnant women had LILA size greater than the respondents who did not consume the milk of pregnant women. Wilcoxon test results significant value or p-value 0.000 <0.05 then there is a significant difference between the nutritional status of pregnant women who consume milk pregnant women with mothers who do not consume milk of pregnant women in BPM Ny.Endang S, or H1 mean is accepted. Although not mandatory, pregnant women are also encouraged to drink 2 glasses of milk per day, because the mother must meet the needs of calcium for the growth of fetal bone and brain